So I know how to simplify something like

\((x+7)(x-7)=x^2-49\)

but can someone give me an easy way to simplify something like

\((2x-3i)(2x+3i)(x+8)(x+2)=?\)

and I'm also going to ask another question about that math problem when I get this answer, so be warned.

Oh! If anyone needs a tip on LaTeX use, message me.

OfficialBubbleTanks
Dec 1, 2017

#1**+3 **

\((2x-3i)(2x+3i)(x+8)(x+2)\\ =(4x^2-9i^2)(x+8)(x+2)\\ =(4x^2+9)(x+8)(x+2)\\ =(4x^2+9)(x^2+10x+16)\\ =4x^2(x^2+10x+16)\quad +\quad 9(x^2+10x+16)\\ etc\)

Melody
Dec 1, 2017

#2

#3**+2 **

Just expand it our and then collect like terms. I thought you cold do that yourself :/

Melody
Dec 1, 2017